The posterior cranial fossa: a comparative MRI-based anatomic study of linear dimensions and volumetry in a homogeneous South Indian population. - Tejus, M.; Kumar, V.; Madhugiri, Venkatesh; Chadha, Awalpreet (Surgical & Radiologic Anatomy, 2015)
Purpose: The posterior fossa contains structures that are vital to life. In this study, we aimed at establishing normal linear dimensions and volume data of the posterior fossa in a homogeneous south Indian population. We also evaluated the influence of large tumors on these parameters. We evaluated the accuracy of different techniques of measuring these dimensions and compared them with literature. Materials and methods: Control and tumor MRIs were selected from an imaging database. Linear posterior fossa dimensions as well as volumes were measured using Image J and Fiji. The volume data were compared with similar data from literature. The effect of the presence of a tumor on posterior fossa volume was measured. Results: The posterior fossa volume was higher in men than in women, irrespective of whether the volume was estimated on axial, sagittal or coronal MR images. Despite the wide variation in the techniques used, there was no significant difference between the volumes reported in literature and the volumes calculated in the current series. The presence of large tumors did not affect linear dimensions or posterior fossa volumes. Among the techniques based on linear measurements that were assessed for concordance with manual segmentation, the technique using the formula for volume of an ellipsoid had the best agreement. Conclusions: Posterior fossa volume is higher in men than in women, Posterior fossa dimensions were not affected by the presence of large tumors. Manual segmentation remains the most accurate method to measure posterior fossa volume.